THE READINESS OF GAPOKTAN SIMPATIK’S ORGANIC RICE FARMERS, MANONJAYA SUB-DISTRICT, TASIKMALAYA REGENCY, IN THE IMPLEMENTATION OF INDUSTRY 4.0 - Talitha Farida Hidayanti; Yayat Sukayat; Dika Supyandi; Iwan Setiawan (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Indonesia is currently entering the 4.0 Industrial Revolution that has the concept of Smart Factories, Industrial Internet of Things, Smart Industry, Advanced Manufacturing, Big Data, and artificial intelligence. The development of the 4.0 industry is agricultural technology. Technology in the field of agriculture is expected to support agricultural productivity in both quantity, quality, and continuity. This research aims to determine the readiness of organic rice farmers in the Gapoktan Simpatik in the implementation of the 4.0 industry. Research was conducted in Gapoktan Simpatik’s farmer, Sub-district Manonjaya, Tasikmalaya District. The research design used quantitative with survey method. The analysis tool used in this research was Mutula & Brakel. The selection of samples in this research used a simple random sampling technique with the formula Slovin of 51 respondents and used the proportional allocation formula to determine the number of samples in each farmer group. Based on calculations using Mutula & Brakel, it showed unprepared results in the Enterprise Readiness. Human Resources Readiness, and ICT Readiness components, while the information Readiness and External Readiness categories were included in the Category ready. Thus, it can be concluded that farmers are still not ready for the implementation of Industrial Technology 4.0.